Peran Komunitas Digital dalam Mempengaruhi Kebijakan Publik (Studi Gerakan Digital seperti Petisi Online atau Forum Aktivisme Netizen) - Ali Mansur; Sarah Pamela (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2026)
The development of digital technology has transformed the landscape of public political participation, creating active digital communities that voice aspirations and influence public policy. This study examines how digital movements, such as online petitions and netizen activism forums, serve as advocacy instruments in Indonesia's policymaking process. Using a descriptive qualitative approach, this research analyzes various real-world cases such as the #SaveKPK, #ReformasiDikorupsi, and #GejayanMemanggil movements, which demonstrate the power of mobilization and consolidation within digital communities. The findings indicate that digital participation expands political access, increases public awareness, and can exert significant political pressure. However, its effectiveness is still limited by low digital literacy, opinion polarization, and the absence of regulations that formally support digital engagement. Therefore, strengthening infrastructure and policies to accommodate digital participation is necessary for democracy to grow more inclusively and responsively in the digital era.